Fallende Körper: Sujet, Motivierung und Handlungsmuster im ‘Eulenspiegelbuch’ - Urban, Felix (Daphnis, 2020)
Abstract It is part of the standard repertoire of Eulenspiegel research to point out that the jest novel Ein kurtzweilig Lesen von Dil Ulenspiegel (1510/15) places a highly contradictory protagonist of heterogenous motivations at the centre of its plot, which oscillates between vita and episode sequence. Rarely, however, have the instruments of structuralist narratology been used systematically to investigate how this heterogeneity and contradiction comes about and what strategies the text uses to connect the individual episodes. Using the example of the recurring element of ‘falling bodies’, this article analyzes the eventfulness, the production of coherence and the function of certain action patterns in the individual episodes. One central hypothesis of this article is that by means of recurrence and variation falling bodies establish a literary paradigm in the novel keeping a central theme of the text present: the dissociation of a superior protagonist who eludes the demands of the community on his body.
Gesehen am 15.02.2021